A stercoral perforation of the descending colon - Kang, Jeonghyun (The Korean Surgical Society, 2012)
This is a case report on a stercoral perforation of the descending colon that was not adequately treated in the first operation. Re-operation was required in order to revise the primary repair site and to remove the impacted fecaloma.